Determinant of matrix 1

Algebra Level 1

If det ( 1 a 2 b ) = 4 \det\left(\begin{array}{cc}1& a\\2& b \end{array}\right)=4 and det ( 1 b 2 a ) = 1 , \det\left(\begin{array}{cc}1& b\\2& a \end{array}\right)=1, what is a 2 + b 2 ? a^2+b^2?


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

det ( 1 a 2 b ) = 4 \det\left(\begin{array}{cc}1&a\\2&b \end{array}\right)=4 \color{#3D99F6}\large \implies b 2 a = 4 b-2a=4 ( 1 ) \color{#D61F06}(1)

det ( 1 b 2 a ) = 1 \det\left(\begin{array}{cc}1&b\\2&a \end{array}\right)=1 \color{#3D99F6}\large \implies a 2 b = 1 a-2b=1 ( 2 ) \color{#D61F06}(2)

From ( 1 ) \color{#D61F06}(1) , we get

b = 4 + 2 a b=4+2a

Substitute the above equation in ( 2 ) \color{#D61F06}(2) , we have

a 2 ( 4 + 2 a ) = 1 a-2(4+2a)=1

a 8 4 a = 1 a-8-4a=1

3 a = 9 -3a=9

a = 3 a=-3

It follows that, a 2 = 9 a^2=9 .

Solving for b b , we have

b = 4 + 2 ( 3 ) b=4+2(-3)

b = 4 6 b=4-6

b = 2 b=-2

It follows that, b 2 = 4 b^2=4

Finally,

a 2 + b 2 = 9 + 4 = a^2+b^2=9+4= 13 \color{plum}\boxed{\large13}

Victor Porto
Oct 9, 2014

(I) -2a + b = 4

(II) 2a - 4b = 2

-3b = 6

b = -2


(I) -4a + 2b = 8

(II) a - 2b = 1

-3a = 9

a = -3


a² + b²

9 + 4

13

K P
Feb 26, 2019

solving determinants give b-2a=4 (1) and a-2b=1 (2). From (1)-(2) we have -3×(a-b)=3 => (a-b)^2=1.and (1)×(2) gives (ab- 2b^2-2a^2+4ab)= 4×1
=> ab-2(a-b)^2= 4
=> ab-2×1=4 => ab=4+2=6 =>2×ab =2×6=12.
Now (a-b)^2=1. {from(1)-(2)} =>a^2 +b^2-2ab=1 => a^2 + b^2 = 1+ 2ab =1+12=13


{ det ( 1 a 2 b ) = 4 b 2 a = 4 . . . ( 1 ) det ( 1 b 2 a ) = 1 a 2 b = 1 . . . ( 2 ) \begin{cases} \det \begin{pmatrix} 1 & a \\ 2 & b \end{pmatrix} = 4 & \implies b - 2a = 4 & ...(1) \\ \det \begin{pmatrix} 1 & b \\ 2 & a \end{pmatrix} = 1 & \implies a - 2b = 1 & ...(2) \end{cases}

2 × ( 2 ) : 2 a 4 b = 2 . . . ( 2 a ) ( 1 ) + ( 2 a ) : 3 b = 6 b = 2 ( 2 ) : a 2 ( 2 ) = 1 a = 3 \begin{aligned} 2 \times (2): \quad 2a-4b & = 2 & ...(2a) \\ (1)+(2a): \quad -3b & = 6 \\ \implies b & = -2 \\ (2): \quad a - 2(-2) & = 1 \\ \implies a & = -3 \end{aligned}

a 2 + b 2 = ( 3 ) 2 + ( 2 ) 2 = 9 + 4 = 13 \implies a^2 + b^2 = (-3)^2 + (-2)^2 = 9 + 4 = \boxed{13}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...